Life Cycle Impact Assessment of Solution Combustion Synthesis of Titanium Dioxide Nanoparticles and Its Comparison with More Conventional Strategies. Issue 8 (27th February 2023) - Rosa, Roberto; Paradisi, Enrico; Lassinantti Gualtieri, Magdalena; Mugoni, Consuelo; Cappucci, Grazia Maria; Ruini, Chiara; Neri, Paolo; Ferrari, Anna Maria
Abstract: This paper represents the first attempt to quantitatively and reliably assess the environmental sustainability of solution combustion synthesis (SCS) with respect to other soft chemistry strategies, which are more conventionally employed in the preparation of engineered oxide nanomaterials, namely hydrolytic and non‐hydrolytic sol–gel syntheses (i. e., HSGS and NHSGS). Indeed, although SCS is well known to rely on significant reduction in the energy as well as time required for the obtainment of the desired nanocrystals, its quantitative environmental assessment and a detailed comparison with other existing synthetic pathways represents an absolute novelty of high scientific desirability in order to pursue a more sustainable development in the inorganic chemistry as well as materials science research fields. TiO2 nanoparticles were selected as the material of choice, for the production of which three slightly modified literature procedures were experimentally reproduced and environmentally evaluated by the application of the comprehensive life cycle assessment (LCA) methodology. Particularly, SCS was compared from an environmental perspective with sol–gel approaches performed both in water and in benzyl alcohol. The results of the present study were also framed among those recently obtained in a systematic study assessing seven further chemical, physical, and biological routes for the synthesis of TiO2 nanoparticles, comprising also flame spray pyrolysis (typically used in industrial productions), highlighting and quantifying the excellent environmental performances of SCS. Abstract : Which is greener : Life cycle assessment methodology demonstrated the environmental sustainability of solution combustion synthesis (SCS) of TiO2 nanoparticles with respect to more conventional hydrolytic sol–gel synthesis (HSGS) and non‐hydrolytic sol–gel synthesis (NHSGS).